SCEPTICISM IN AFRICA: AN EPISTEMIC CUM AFRICAN PHILOSOPHICAL TRAJECTORY - Elias Ifeanyi E. Uzoigwe (Universitas Negeri Makassar, 2020)
In this work, I will be exploring the possibility of African skepticism in the philosophical milieu, and also in advancing the course of African philosophical discourse. This will be the underlying focus of this study. Employing the terms epistemic and trajectory is a way of trying to show that though skepticism is the fulcrum or pedestal upon which epistemology springs up as a branch of philosophy, however, the fact remains that African scepticism is not wishful thinking but a reality. Some of the philosophers of African descent whose works prove the existence of African scepticism like Hountondji, Asouzu, Wiredu, Oruka, and a host of others deserve grateful acknowledgment. It is in the process of other African philosophers’ objective reactions, critiques, criticisms and counter criticisms to their sceptical views that African philosophy, African philosophers and African skepticism are powerfully made more evident as realities in the philosophical enterprise. This work strongly holds that the attitude of undermining the efforts of African philosophers by fellow African scholars should be discouraged, rather the mindset should be that of African philosophical ecumenism where each scholar and school collaborate and corroborate with others to synergise for the advancement of thoughts and ideas that are indigenous to Africa, enrich and employ them in tackling the problems that are facing African and still extend generous hands of assistance in tackling the global challenge.